Deteksi Dini Faktor Resiko Remaja Putri Melalui Pemeriksaan Kesehatan Sederhana Sebagai Implementasi Interprofesional Colaboration (IPC) - Yulien Adam; Atik Purwandari; Anita Lontaan; Agnes Montolalu (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
This community service activity aimed to detect early health risk factors among adolescent girls through simple health screenings and to enhance students' awareness of healthy living using an Interprofessional Collaboration (IPC) approach. The methods included basic physical examinations, body mass index (BMI) measurements, mid-upper arm circumference (MUAC), blood pressure checks, and dental health evaluations. The activity was conducted in April 2025 at Dormitory Campus A of Poltekkes Kemenkes Manado, involving 45 students from various study programs. The results showed that 31.1% of participants suffered from Chronic Energy Deficiency (CED), 35.8% had underweight status, 22.2% were classified as thin, and 13.4% were overweight or obese. Additionally, 35.8% of the students had low blood pressure, while 64.4% were in the ideal weight category. The program also provided nutrition education, promoted healthy eating patterns, and distributed iron tablets. These findings highlight the need for continuous interventions in the form of health education and monitoring. In conclusion, the IPC approach is effective in detecting health problems among adolescent girls while improving students' knowledge and attitudes towards their personal health.